Antimicrobial resistance of bacterial pathogens isolated from cancer patients: a systematic review and meta-analysis - Onyansaniba K. Ntim; Aaron Awere-Duodu; Abdul-Halim Osman; Eric S. Donkor (BMC Infectious Diseases)
Abstract Background Antimicrobial resistance (AMR) is a major threat to global public health, limiting treatment options for infections. AMR is particularly life-threatening for cancer patients, who are at increased risk of antibiotic-resistant infections. This review presents the first comprehensive data on the prevalence of AMR in major bacterial pathogens isolated from cancer patients. Method An extensive search was conducted in PubMed, Scopus, and Web of Science, focusing on studies published in English from 2000 to 2024. A single-group meta-analysis was performed to determine the resistance prevalence of major bacterial species. Results One hundred thirty-two full-text articles were included in the systematic review, and studies on haematological cancer patients were the most common (36.4%). The major bacterial pathogens reported were Escherichia coli, Klebsiella pneumoniae, Staphylococcus aureus, Acinetobacter baumannii, Pseudomonas aeruginosa, Enterococcus faecium, Streptococcus pneumoniae and Enterobacter spp. For E. coli, resistance prevalence was highest for penicillins (81.84%), followed by cotrimoxazole (65.79%) and monobactams (61.61%). For K. pneumoniae, the highest prevalence of resistance was observed for penicillins (98.99%), followed by cotrimoxazole (70.92%). Acinetobacter baumannii had high resistance prevalence to multiple antimicrobial classes, including third-generation cephalosporins (84.10%), fourth-generation cephalosporins (80.75%), carbapenems (82.58%), fluoroquinolones (80.37%), beta-lactam-beta-lactamase inhibitors (79.15%), cotrimoxazole (75.77%), and aminoglycosides (64.05%). Enterobacter spp. and Enterococcus faecium showed high resistance prevalence to penicillins at 91.77% and 90.64% respectively. P. aeruginosa had a high prevalence of resistance to third-generation cephalosporins (49.41%) while S. aureus showed high prevalence to macrolides (55.63%) and methicillin (45.29%). Conclusion This review indicated a high prevalence of antimicrobial resistance in bacterial pathogens isolated from cancer patients worldwide. The pronounced resistance prevalence observed, especially among ESKAPE pathogens, underscores the urgent need to improve infection prevention and antimicrobial stewardship in cancer care globally.